Strengthening Competitiveness of Korean Testing, Inspection, and Certification Institutions for Global Market Expansion (aSSIST Business Review, 2026)
(1) Background/Purpose: The global Testing, Inspection, and Certification (TIC) market is expanding at a compound annual growth rate of approximately 3.3–5.0%, driven by tightening international regulations, the rise of renewable energy and healthcare industries, and accelerating digital transformation. Korean TIC institutions, however, remain disproportionately concentrated in the domestic market, constrained by structural deficiencies in skilled human resources, testing equipment, and international networks, while facing intensifying competition from global TIC leaders such as SGS, TÜV SÜD, and Bureau Veritas operating within Korea. (2) Methodology: This study employs a mixed-method approach. Quantitative analysis uses One-Way ANOVA (Welch’s) and Games-Howell post-hoc tests applied to the 2023 Korea Testing and Certification Industry Association (KOTICA) national survey data (n = 7,889 institutions), segmented into eight revenue-size groups, to identify statistically significant differences in competitiveness perceptions and equipment holdings. Qualitative analysis benchmarks the training programs of the Korea Testing and Research Institute (KTR) Academy against the SGS Academy, and applies a SWOT framework to the Korean TIC industry. (3) Findings: Statistically significant differences were confirmed across all eight revenue groups for four competitiveness dimensions (capability/scope, expert staff, investment scale, external reputation; all p < .0001). Equipment holdings differ significantly by revenue group (p < .0001), with institutions generating under 100 million KRW holding an average of 5 equipment types compared to 278 for the 20–30 billion KRW group. KTR Academy offers 30 programs, primarily domestic-standards-focused, compared to SGS Academy’s 85 programs spanning international standards, digital technologies, and online delivery. SWOT analysis reveals that strong manufacturing demand and government support constitute key strengths, while outdated infrastructure, skills shortages, and limited international networks are principal weaknesses. (4) Originality/Value: This study provides the first systematic empirical analysis of the Korean TIC industry’s competitiveness gap using large-sample ANOVA, and derives evidence-based strategic recommendations covering human resource development, equipment modernization, and diversified business and marketing strategies.
Keywords: testing; inspection; and certification (TIC); Korean TIC industry; global competitiveness; ANOVA; human resource development; digital transformation; SWOT analysis; SGS; accreditation